Anticipating Mechanical Ventilation In Children With Guillain –Barre Syndrome And Improving Outcome Of The Illness - Al-janabi, Muhi K. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Acute inflammatory demylinating polyneuropathy (Guillain-Barr’e syndrome) is the commonest cause of acute neuromuscular paralysis in most countries. The onset of symptoms in patients with GBS can either be acute or sub acute .Ventilatory failure is primarily caused by inspiratory muscles weakness although weakness of abdominal and accessory muscles of respiration, retained airway secretion leading to aspiration and atelectasis are all contributing factors. Nutritional support of critically sick children is important for metabolic maintenance and tissue repair. Methods: To identify clinical and respiratory features associated with progression to respiratory failure in children with GBS. Twenty two consecutive children with severe (Rapidly progressive) GBS admitted to the RICU in Children Welfare Teaching Hospital-Medical City –Baghdad, between July 2004-July 2006, were studied .Other 22 children with sub acute GBS who didn’t receive mechanical ventilation admitted in the same period to the same hospital as a control group. Results: There is significant association between each of bulbar, autonomic neuropathies and low SiO2 at admission with severe GBS .There is significant reduction in duration of mechanical ventilation and duration of RICU stay achieved by the use of Freamine amninoacid solution as partial parenteral nutrition. Conclusion: Progression to mechanical ventilation was highly likely to occur in those patients with rapid disease progress (less than one week) bulbar dysfunction and dysautonomia, and low SiO2 at admission. Partial parenteral nutrition may reduce the duration of mechanical ventilation and RICU stay by about 3 days.